Sentinelas do sudoeste : o exército brasileiro na fronteira paranaense - Zatta, Ronaldo (2009)
This work had the intention to analyze the influence of the army in regional training society in the southwest paranaense. The history of colonialism regional be confused with the military organizations that were highlighted in the region, for this reason were directed efforts to understand how gave good social coexistence between military and pioneers resulted in a political identity common to all. The start of the analysis is given in the area of "geopolitics" studying the thoughts of ESG on the region (border with Argentina and next to Paraguay) still in twenty years, following in the field of "political culture" and "social imaginary" for to explain the fraternal relationships created, the good local life and the identification as a social group with roots in common. The proximity to the border and the presence of military institutions through their hearings in times of colonization (Revolt in 1957) with their symbols, mores and rituals symbolic of civism have marked with traces of "nationalism" the social basis in the region. Lastly the studies pointed to the field of the "memory", which holds forth on the lieutenant Camargo, military transformed into hero regional after have been killed in combat the guerrilla movement in 1965. I believe that this miscellanies historiographical provided different perspectives that better developed the main objective, to study the influence of casern training sudoestina society